Combination of Epidural Morphine and Fentanyl for Postoperative Analgesia. Issue 4 (July 1991) - Tanaka, Makoto; Okane, Masato; Watanabe, Seiji; Hamaya, Yoshihiro; Endo, Takuo
Abstract : The rapid onset of epidural fentanyl could be used to cover the latency period of epidural morphine, thus potentiating analgesia during anesthesia regression after short-acting local anesthetics and possibly extending morphine analgesia for longer duration. The object of this study is to determine whether there are clinical advantages or disadvantages of combining epidural morphine and epidural fentanyl for postoperative analgesia. Patients scheduled for gynecologic procedures were assigned to two groups ( n = 54 for each): Group 1 receiving 4 mg epidural morphine, and Group 2 receiving 4 mg epidural morphine and 100 μg fentanyl 30 minutes before the estimated completion of the surgery using lidocaine epidural anesthesia. Comparisons were made with regard to: (1) times before the first supplemental analgesic for incisional pain, (2) numbers of supplemental analgesic during the first 48 hours postoperatively, and (3) adverse effects. The two groups were comparable. The number of patients requiring supplemental analgesics between the fourth and 17th hours was significantly greater in Group 1 ( n = 10, compared to n = 0 for Group 2; p < 0.05). The mean time before the first supplemental analgesic was significantly longer in Group 2 ( p < 0.05). The number of supplemental analgesics during the first 48 hours was significantly less in Group 2 ( p < 0.01). No significant difference was found regarding adverse side effects. The results obtained confirm the potential desirability of combining epidural morphine and epidural fentanyl for postoperative analgesia.